A secure authentication protocol for wearable devices environment using ECC. (August 2019) - Kumar, Devender; Grover, Harmanpreet Singh; Adarsh
Abstract: One of the challenging issues in wearable devices environment is to provide a secure communication. User authentication is a mechanism which is used to provide the secure communication in this environment. In this paper, we propose an authentication protocol for wearable devices environment using elliptic curve cryptography (ECC). We analyze the formal security of our scheme using random oracle model and discuss its informal security analysis to show that it is resistant to various known attacks. We formally verify its security using the ProVerif tool. Our scheme performs better than the existing related schemes in terms of security features and communication cost.